Needs of Stakeholders in Fast-Track Care for ST-Segment Elevation Myocardial Infarction (STEMI) - Sungbun, Songwut; Piaseu, Noppawan; Partiprajak, Suphamas (Journal of Thailand Nursing and Midwifery Council, 2018)
Objective: To describe needs of stakeholders in fast-track care for ST-segment elevation myocardial infarction (STEMI). Design: Descriptive qualitative research. Methodology: The participants in this study were selected via purposive sampling and divided into two groups: (1) patients and/or their relatives (n = 30) in fast-track care for STEMI; and (2) healthcare providers (n = 20). Data were collected using semi-structured interviews, observation and feld notes, and were analysed using content analysis. Results: Needs of the patients and/or their relatives included 1) information and communication (information on STEMI, on severity of STEMI symptoms and on the need to seek medical attention; communication; and shared decision making), and 2) psycho-social support (fnancial compensation during ACS event, moral support, a supportive environment, and support by family members). Meanwhile, needs of healthcare providers in STEMI fast-track care included 1) critical care skill (early detection, skill enhancement, increased competency of care for patients with STEMI); 2) effective organisational management (increased budget, suffcient workforce, and suffcient cardiologists); 3) medical equipment support (stability of equipment, and communication through medical service networks); and 4) effectiveness of the caregiving system (effective use of the EMS, appropriate and effective communication, effective guideline-based strategies, and effective risk management and proper insurance coverage for accident victims). Recommendations: The results of this study can be used to improve STEMI fast-track service, particularly by providing information on specifc signs and symptoms of STEMI, to help patients realise their conditions and decide to receive early care. Nurses should focus on developing effective and cross-cultural communication to promote positive nursing outcomes. Regarding risk management, the system of providing accident victims with proper insurance coverage and compensation should be developed based on the context of each hospital, to ensure an effective practice.